2011
DOI: 10.1007/978-1-61779-445-2_23
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Reaction Monitoring for the Accurate Quantification of Amino Acids: Using Hydroxyproline to Estimate Collagen Content

Abstract: Multiple reaction monitoring (MRM) mass spectrometry may be regarded as the gold standard methodology for quantitative mass spectrometry and has been adopted for the analysis of small molecules especially within the pharmaceutical industry. It can also be applied to the analysis of peptides and proteins and to the measurement of the basic building blocks of proteins, amino acids. Here, we describe the application of MRM mass spectrometry to the measurement of hydroxyproline after acid hydrolysis of various ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 10 publications
1
6
0
1
Order By: Relevance
“… 28 Further analyses also revealed that the administration of compound 6j caused a dose-dependent suppression in the content of hydroxyproline ( Figure 5 C), a unique amino acid found in collagen. 29 The above data collectively indicate the promising therapeutic potential of 6j against the BLM-induced pulmonary fibrosis.…”
Section: Resultsmentioning
confidence: 78%
“… 28 Further analyses also revealed that the administration of compound 6j caused a dose-dependent suppression in the content of hydroxyproline ( Figure 5 C), a unique amino acid found in collagen. 29 The above data collectively indicate the promising therapeutic potential of 6j against the BLM-induced pulmonary fibrosis.…”
Section: Resultsmentioning
confidence: 78%
“…Hydroxyproline is formed only as a post‐translational modification in the peptide chain, and proline hydroxylase does not hydroxylate free proline. Hydroxyproline levels in tissue hydrolysates are a direct measure of the amount of collagen or gelatin present (Colgrave et al ., ). A variety of disease states are believed to affect collagen turnover and can cause elevated serum or urine hydroxyproline levels.…”
Section: Discussionmentioning
confidence: 97%
“…Hydroxyproline can be used as an index of protein quality (49), due to its being a marker of collagen content (50). The levels of collagen and of hydroxyproline were higher in the control diet compared with the BSF diet, probably due to the fact that collagen is limited in insect meal compared to that in vertebrate protein meal.…”
Section: Discussionmentioning
confidence: 99%